ISLAM IN INDIA DURING THE MUGHAL DYNASTY TO THE ERA OF BRITISH RULE - Taufik, Bella Riskika; Faiz, Muhammad (Annual International Conferences on Language, Literature, and Media; No 1: 3rd AICOLLIM (Annual International Conference on Language, Literature, and Media), 2021)
During the Middle Ages, Islamic rule was concentrated in three prominent kingdoms, the Ottoman Dynasty in Turkey, the Safavid Dynasty in Persia, and the Mughal Dynasty in India. This paper will explore the history of Islam that developed in India in three periods, first from the period before the Mughal Empire came to power, the second when the Mughals ruled India, and the third when British imperialism began to dominate India. This research was carried out using a library research type method, which supports the study of the development of Islam in India from 705 to 1947 AD. This study shows that Islam developed rapidly in India when the religious conditions of the people rivaling each other between Hindus and Buddhists weakened their influence when the Mughals came to power. As a result, Islam grew by applying Islamic teachings and high values ​​of tolerance even though the Muslim population was still a minority compared to Hindu-Buddhist. When Britain entered India, the condition of the Islamic government continued to weaken, including the weak of leadership after the Aurangzeb era, the struggle for power between regional Muslim leaders at the central level, and the emergence of separatist movements from Hindu groups in several areas to facilitate the British invasion of India.